(untitled) (Annals of Medical Research, 2021)
Aim: The study’s aim was to compare the effects of norepinephrine, ephedrine, and 0.9% sodium chloride (NaCl) solution against the hemodynamic response that develops after spinal anaesthesia. Materials and Methods: The study was conducted on 80 patients who were scheduled for surgery onlower extremity varicose veins, and they were divided into four groups. Group F was started with a 0.9% NaCl solution of 15ml/kg 20 minutes before spinal anaesthesia. For 20 minutes after spinal anaesthesia, Group E received 2mg/min of ephedrine and Group N received 5mic/min norepinephrine as an infusion. Meanwhile, Group C was not given any medication or fluid. Spinal anaesthesia was performed with 0.5% bupivacaine. The systolic blood pressure (SBP), diastolic blood pressure (DBP), heart rate (HR), and peripheral oxygen saturation (SPO2) values of the patients were recorded before and after the procedure. Sensorial block levels and degrees of motor block were also recorded after the operation. In addition, side effects other than hypotension that may develop after the surgery were also recorded. Results: There was no statistically significant difference between the groups in terms of SBP, DBP, SPO2, HR, sensory block level, and degree of motor block (p>0.05). In Group C, the decrease in SBP and DBP values that occurred at the fifteenth, twentieth, and thirtieth minutes of spinal anaesthesia was statistically significant when compared with the control values (SBP: p=0.0274, 0.0028, 0.0036, and DBP: p=0.0132, 0.0210, 0.0041). Hypotension developed in 10 (50%) of the 20 patients in Group C, and a 10mg intravenous (IV) bolus intervened with ephedrine. This result was statistically significant when compared with Group F, Group E, and Group N (p=0.005). Conclusion: As a result, it has been shown that norepinephrine, ephedrine, and 0.9% NaCl solution are similarly effective in preventing hypotension from developing after spinal anaesthesia.